PENGARUH INFRASTRUKTUR DAN KELEMBAGAAN TERHADAP KINERJA EKSPOR AGREGAT DAN SEKTORAL INDONESIA - Zenal Asikin; Arief Daryanto; Lukytawati Anggraeni (School of Business, Bogor Agricultural University (SB-IPB), 2016)
Export performance of a country is influenced by many aspects, some of which include infrastructure and institutionalization. The major problem that is faced by Indonesia is the low quality of infrastructure and institutionalization; as a result, the trading cost is relatively high. If this is not dealt immediately, it will cause a decline in the Indonesian export performance. This research was aimed to analyze the influence of infrastructure and institutionalization as well as other related variables on the performance of aggregate export, agricultural materials, foods, and manufactures of Indonesia. The research used secondary data with time series between 2005 and 2013 and cross-section of the Indonesian export main target countries. The research used a gravity model with fixed-effect estimation methods. The results of the research showed that infrastructure and institutionalization as well as other related variables influenced the Indonesian export flows. Based on the findings mentioned above, in order to increase Indonesian export, it is important to improve the infrastructure and institutionalization performances that are related, firstly, to the capacity and quality of transportation infrastructure, especially roads and ports; secondly, to optimization of communication information technology, especially the use of e-marketing; thirdly, to increased quality of Indonesian governance, especially control of corruption, rule of law, regulatory quality and government effectiveness; and fourthly to acceleration of export duration and simplification of export permit document. Furthermore, Indonesia needs to review its import tariff policy that applies to export target countries and also review whether it is necessary to improve domestic support.Keywords: export, gravity model, infrastructure, institutionalization